Efektivitas Kebijakan Perlindungan Anak di Era Digital - Eviani Masruroh; Miftakhul Jannah; Yes Matheos Lasarus Malaikosa (Jurnal Ilmu Sosial dan Humaniora, 2024)
This article examines the effectiveness of child protection policies in the digital era. The purpose of this literature review is to evaluate the implementation and impact of existing policies in protecting children from potential dangers in the digital environment. Data collection and analysis techniques for a literature review involve identifying, selecting, critically evaluating, and synthesizing relevant information from various trusted sources to answer specific research questions. The results of the study indicate that although there have been efforts to protect children in a regulatory manner, there are still challenges in effective enforcement and supervision. The gap between policies and implementation in the field, as well as the lack of collaboration across stakeholders are the main issues that need attention. This study concludes that there is a need to review and improve child protection policies in the digital era, as well as strengthen synergy between government, industry, and society to create a safe digital environment for children.